Investigating P300 Response In Visual Searching Of Multiple Traffic Objects During Driving - Yamamoto, Yuki; Kurahashi, Kohma; Wagatsuma, Nobuhiko; Nobukawa, Sou; Inagaki, Keiichiro (Society of Visual Informatics, 2025)
Traffic accidents associated with visual errors such as misperception and carelessness continue to account for a significant proportion of traffic accidents. In traffic scenes, several types of traffic objects exist; therefore, drivers should pay attention to these objects for their recognition and safe driving decisions. Drivers need to allocate their visual attention resources to these objects because their recognition is closely related to safe driving behavior. Recent studies unveiled that attention-related event-related potentials (ERPs), specifically the P300, were observed in drivers’ electroencephalography, and its response characteristics varied with the intensity of attention. However, the factors of information inherent in traffic objects and driving behaviors remain mysteries. To understand the attention-related ERP P300 during visual searching of multiple objects while driving, we measured the P300 responses during vehicle driving using a driving simulator. We examined its response characteristics, especially in relation to types of traffic objects, considering drivers’ actions toward them and their capacity to induce visual attention. The results showed that the occurrence of P300 during multiple visual searches depended on the types of traffic objects, indicating that certain traffic objects more easily induced P300 responses from drivers, thereby attracting their attention. Moreover, we found that traffic objects that prompt driving actions are essential factors in their capacity to induce attention. By computational simulations of visual perception during driving using a model that can reproduce visual attention, further mechanisms of visual attention and the relationship between driving maneuvers and P300 responses will be understand.